Monetary Policy and Asset Prices: When Cleaning Up Hits the Zero Lower Bound - Wolfram Berger; Friedrich Kissmer (Swiss Journal of Economics and Statistics, 2013)
Recently, convincing evidence has been presented that the recession in the wake of the recent financial crisis resulted primarily from an overly levered housing sector that was forced to deleverage and cut consumption spending when faced with collapsing housing prices. Following this interpretation it is argued that, as opposed to the consensus view on monetary policy in the vicinity of the ZLB, optimal monetary policy may involve an interest rate increase if the ZLB threatens to become a binding constraint in the aftermath of an asset price bust. This result delivers arguments to advocate a in the previous literature less favored pre-emptive tightening policy in an asset price boom.
Keywords: E52; E58; E44; 330; monetary policy; asset price bust; zero lower bound; cleaning-up; pre-emptive tightening